Eksistensi Pola Hidup Dan Budaya Masyarakat Banten Di Tengah Era Globalisasi - Nurhadi - ASM BSI Jakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2012)
After a major disaster occurs the Krakatau volcanic upheaval of cultural fusion between the region into a funnel changing mores of civilization, more rapid global flows in all areas of culture will be eroded by the advance of civilization itself towering hills with thatched safananya rice fields with a broad expanse of banana trees , coconut, a bamboo is so remedy, settlement houses and a bamboo thatched roof rumbiya disappear without leaving a trace, every month held a prayer every mosque now only the name of the clergy and congregation qodiriyah Naqsyabandiyah eroded one by one change in the era of take-off time has eroded the generation shift factor present into memories of changing times. the climate became hot jelagat erratic jet black skin, the water becomes a channel of the rulers arbitrarily killing people en masse to be poor structural delicious he sat on a wet field will not be afraid to rebel again each other.The series shows the beauty of the beach like knick knacks and glittering diamonds sparkle metropolotan beauty of the city but does not belong to the citizens in general offerings solely unused money to the top, the challenge facing him like an enemy to challenge an invincible warrior who never theKrakatau child .The Banten in his second term it after the Nangro Aceh Darusalam uphold the teachings of the classics that brought its predecessor. Will the public offerings will change the mindset whereas the domicili to the Banten diaspora groups to host a guest while the native land of his own, offerings a priority progress of civilization up to the hindia empire until kerepublik dutch. Leadership is only for lobbying and protection of investors rather than native sefty number one is not prioritized, as a result of race kehegominition the Pandeglang neglected citizens become less marginalized citizens the Rangkas bitung (lebak) looking structural poverty, the Tangerang contaminated with various interests of the feudalistic. Could it be according to classic predecessors mitolgi theSundanese traditional ancestor witwitan assume that the embryo of marginalized indigenous people will immigrate to the Ujungkulon while they has become a national park ownership is recognized by all countries to donors on they towards sustainability. Keywords: Way Of Life, Culture, Globalization